2018
DOI: 10.5194/nhess-18-231-2018
|View full text |Cite
|
Sign up to set email alerts
|

Seismic assessment of a multi-span steel railway bridge in Turkey based on nonlinear time history

Abstract: Abstract. Many research studies have shown that bridges are vulnerable to earthquakes, graphically confirmed by incidents such as the San Fernando (1971 USA), Northridge (1994 USA), Great Hanshin (1995 Japan), and Chi-Chi (1999 Taiwan) earthquakes, amongst many others. The studies show that fragility curves are useful tools for bridge seismic risk assessments, which can be generated empirically or analytically. Empirical fragility curves can be generated where damage reports from past earthquakes are available… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 30 publications
0
6
0
Order By: Relevance
“…Increasingly, aspects of social justice and equity are included in risk assessments to support the selection of optimal damage mitigation measures (Thaler et al, 2018). Two studies included in this special issue underpin this aspect by highlighting the importance of comprehensive event and risk assessments as well as integrated approaches to investigate the interaction of physical and socio-economic processes (Zhang et al, 2017;Markantonis et al, 2018). Additionally, cost assessments may include costs of the recovery phase as households may face enormous difficulties in recovering from events, as shown by Markantonis et al (2018) in this special issue.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Increasingly, aspects of social justice and equity are included in risk assessments to support the selection of optimal damage mitigation measures (Thaler et al, 2018). Two studies included in this special issue underpin this aspect by highlighting the importance of comprehensive event and risk assessments as well as integrated approaches to investigate the interaction of physical and socio-economic processes (Zhang et al, 2017;Markantonis et al, 2018). Additionally, cost assessments may include costs of the recovery phase as households may face enormous difficulties in recovering from events, as shown by Markantonis et al (2018) in this special issue.…”
Section: Discussionmentioning
confidence: 99%
“…The results show that reduction of the window openings affected the structural behaviour of the mosque positively. Zhang et al (2017) analyse the ripple effects of indirect economic damage and spatial heterogeneity of both direct and indirect economic damage caused by a hypothetical earthquake in the region of Beijing, China. Spatial heterogeneity of damage is analysed at the scale of streets, villages and towns.…”
Section: Damage Assessment and Mitigationmentioning
confidence: 99%
See 1 more Smart Citation
“…Kumar and Gardoni [9] proposed probabilistic models to predict the effect of past earthquakes on the structural properties of RC highway bridge columns and their steel reinforcement, and then developed degradation models were used to assess the effects of seismic degradation on the seismic vulnerability of a RC highway bridge with one single-column bent. Yılmaz and Çağlayan [10] used both lateral displacement limit state and capacities of its structural members to derive fragility curves of a multi-span simply supported steel truss railway bridge. Pela et al [11] performed nonlinear static (pushover) analysis and nonlinear time history analyses for seismic capacity assessment of an existing brick masonry triple-arched bridge and showed that the pushover results can slightly overestimate the time-history average predictions.…”
Section: Introductionmentioning
confidence: 99%
“…Other test was also conducted to see the vulnerability of the railway bridge [18], while structure damage detection is also proposed by its dynamic characters in other study [19]. Many other research related to steel truss bridges under seismic namely in Turkey [20] and for pedestrian bridges [21]. Beside the seismic load, the moving load also became a factor that give the vibration or dynamic activity in the bridge [22].…”
Section: Introductionmentioning
confidence: 99%